2018
DOI: 10.1016/s1473-3099(17)30725-9
|View full text |Cite
|
Sign up to set email alerts
|

Post-exposure prophylaxis with doxycycline to prevent sexually transmitted infections in men who have sex with men: an open-label randomised substudy of the ANRS IPERGAY trial

Abstract: France Recherche Nord & Sud Sida-HIV Hépatites (ANRS) and Bill & Melinda Gates Foundation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
183
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 253 publications
(188 citation statements)
references
References 27 publications
3
183
0
2
Order By: Relevance
“… and Molina et al . have reported the successful use of doxycycline prophylaxis to reduce the incidence of syphilis and chlamydia in high risk MSM. Doxycycline was not effective for prevention of gonorrhoea.…”
Section: Discussionmentioning
confidence: 99%
“… and Molina et al . have reported the successful use of doxycycline prophylaxis to reduce the incidence of syphilis and chlamydia in high risk MSM. Doxycycline was not effective for prevention of gonorrhoea.…”
Section: Discussionmentioning
confidence: 99%
“…These behavioural changes could result in condom use for some individuals, however, there are other interesting alternatives such as partner notification or BI for STIs. Recent studies on the prophylactic use of doxycycline for bacterial STIs have shown promising results post‐exposure and used daily , but remain to be confirmed in studies with longer follow‐up . Use of doxycycline may be particularly pertinent among PrEP users who experience recurrent STIs; a recent analysis has shown that among MSM PrEP users, 25% participants accounted for a little more than three‐quarters of all STIs .…”
Section: Discussionmentioning
confidence: 99%
“…POCTs will increase the uptake of STI screening in vulnerable populations that are at highest risk and will have an impact on detection and treatment. [123][124][125][126].…”
Section: Discussionmentioning
confidence: 99%
“…As already noted, HIV PrEP trials have found high incidence of classical STIs [96][97][98]104]. Bolan et al [124] and Molina et al [125] have reported the successful use of doxycycline prophylaxis to reduce the incidence of syphilis and chlamydia in high risk MSM. Doxycycline was not effective for prevention of gonorrhoea.…”
Section: Prep For Stismentioning
confidence: 99%